A Review on Microwave Baking of Foods (International Journal of Innovative Research in Computer Science & Technology, 2021)
Microwaves communicate with polar  atoms and charged particles of food to produce heat. There  are contrasts between the warming instruments of  microwave and traditional warming. The utilization of  microwave warming enjoys the benefit of saving energy  and time, working on both nourishing quality and  agreeableness of certain food varieties by purchasers.  Microwaves are effectively utilized both in homes and in  the food administration industry. Be that as it may, there  are still issues in consummating microwave baking, along  these lines it is a well-known exploration region. The  fundamental issues found to happen in microwave prepared food items are low volume, intense or firm  surface, lack of caramelizing and flavour improvement.  Ongoing investigations intend to work on the nature of  microwave-prepared items. This article surveys the  fundamental standards of microwave baking, issues  ordinarily happening in microwave-prepared items lastly  studies distributed concerning microwave baked items.
Keywords: Browning; Bread; Cake; Microwave; Baked Products